Libraries Burning - Phyllis Mauch Messenger (Open Rivers: Rethinking Water, Place & Community, 2024)
By Phyllis Mauch Messenger. For much of the planet, 2023 was the warmest year on record, and the 12 warmest years have all been documented since 2005.[i] The repercussions of this warming pattern, of undeniable climate change, are both dauntingly real and not yet fully knowable, both immediately problematic and also intensifying over time. The article republished here demonstrates a commitment to action and hope in the face of climate change. In 2019, Phyllis Mauch Messenger detailed the work of several archaeological projects across the Arctic region focusing on salvaging materials long held in permafrost landscapes that are at risk due to warming temperatures.